Recent advances in drug substance development – prodrug strategies for enhancing the bioavailability and potency of antiviral nucleosides - Andrzej Kutner (Journal of Medical Science, 2023)
Bioavailability is a prerequisite for drug activity.  In vivo bioavailability (intestinal permeability), linked to drug substance solubility and drug product dissolution, became the basis of Gordon L. Amidon’s Biopharmaceutical Classification System.  One method of improving the drug substance’s bioavailability is to modify its structure chemically, leading to increased lipophilicity and the ability to penetrate the phospholipid bilayer of the cell membrane.  These modifications, known as prodrug strategies, involve derivatizing the drug substance by introducing substituents that reduce the hydrophilicity of the molecule.  The present mini-review outlines the examples of Christopher McGuigan’s prodrug strategies used to obtain antiviral nucleosides with enhanced bioavailability and activity.  These strategies primarily involve forming and optimizing the structure of esters and amino acid esters, phosphoramidates, octadecyl phosphates, and bis-pivaloxymethyl phosphates.  The review discusses the optimization of the phosphoramidate prodrug moiety of the SARS-CoV-2 antiviral nucleoside remdesivir in detail.  It presents the resulting improvement in bioavailability and antiviral activity.  Moreover, it focuses on the modern prodrug strategy as one of the major recent advances in drug substance development.  This strategy effectively optimized physicochemical properties and improved the functional activity of the existing drug substances and drug substance candidates for the first time.